2020
DOI: 10.1080/14737167.2020.1819795
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of adjuvant trastuzumab therapy for HER2-positive early-stage breast cancer: systematic review and quality assessment

Abstract: Introduction: As the availability of new economic evaluations (EE) on adjuvant trastuzumab therapy for early-stage breast cancer (EBC) with HER2-positive since last search and other EEs missed warrant a more extensive review, this study aimed to systematically review EEs of adjuvant trastuzumab compared with chemotherapy alone for HER2-positive EBC. Area covered: The search was performed in February 2019 using MEDLINE and Scopus. Reviewers independently selected studies based on eligibility criteria, extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Regarding the combined administration of biosimilars for HER2+ MBC, Diaby et al showed that trastuzumab with docetaxel as the first line of treatment represented the most cost-effective strategy among the four regimens evaluated in patients with HER2+ MBC [ 72 ]. Genuino et al [ 73 ], in a recent systematic review, evaluated the adjuvant administration of trastuzumab in comparison with chemotherapy alone in patients with HER2+ EBC. They analyzed data from 22 studies from high- and middle-income countries, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the combined administration of biosimilars for HER2+ MBC, Diaby et al showed that trastuzumab with docetaxel as the first line of treatment represented the most cost-effective strategy among the four regimens evaluated in patients with HER2+ MBC [ 72 ]. Genuino et al [ 73 ], in a recent systematic review, evaluated the adjuvant administration of trastuzumab in comparison with chemotherapy alone in patients with HER2+ EBC. They analyzed data from 22 studies from high- and middle-income countries, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, economic effectiveness results from HICs do not translate to LMICs, and even countries within the same income level may have different results depending on the price of medications and availability of real-world data. 44 An example would be the case for pertuzumab. In the HER2-positive adjuvant setting, pertuzumab scored a level C on the Magnitude of Clinical Benefit Scale, which indicates low clinical benefit, whereas in the metastatic setting, it scored a level 4, which indicates a substantial clinical benefit.…”
Section: Price-efficacy Dilemma For Modern Drugs Used To Treat Patien...mentioning
confidence: 99%
“…Specifically, it is sought to present a practical methodology to contrast the clinical impact against the economic impact of patient service management in their different stages in the line of treatment. In recent years, models regarding the cost-effectiveness of breast cancer individual treatments have been made [7][8][9][10][11][12][13] as well as reviews analyzing new therapies' cost-efficiency [14][15][16] . However, during open research, only the study made by Wong et al 16 was found to be like ours.…”
Section: Introductionmentioning
confidence: 99%